2021
DOI: 10.3390/ijerph18041610
|View full text |Cite
|
Sign up to set email alerts
|

A Novel IoT Based Positioning and Shadowing System for Dementia Training

Abstract: A rapid increase in the number of patients with dementia, particularly memory decline or impairment, has led to the loss of self-care ability in more individuals and increases in medical and social costs. Numerous studies, and clinical service experience, have revealed that the intervention of nonpharmacological management for people with dementia is effective in delaying the degeneration caused by dementia. Due to recent rapid developments in information and communications technology, many innovative research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As explained in Section 3.2.4, direct experimentation is not very frequent, and most of the data used in the literature comes from surveys, interviews or case studies. In fact, we can find several calls for more empirical studies in the reviewed papers (e.g., Affolderbach & de Chardon, 2021; Ekener, 2019; Hervani et al, 2022; Hung et al, 2021; Palumbo et al, 2022; Tavares & Azevedo, 2022; Young et al, 2019), with specific examples such as “there is a need for more empirical studies and quantitative research” (in the context of Industry 4.0 and Sustainability) (Mastrocinque et al, 2022) or the remark from (Grybauskas et al, 2022) about the “sheer lack of empirical evidence on the positive or negative impacts of Industry 4.0 on social sustainability”.…”
Section: Discussion and Future Research Agendamentioning
confidence: 99%
“…As explained in Section 3.2.4, direct experimentation is not very frequent, and most of the data used in the literature comes from surveys, interviews or case studies. In fact, we can find several calls for more empirical studies in the reviewed papers (e.g., Affolderbach & de Chardon, 2021; Ekener, 2019; Hervani et al, 2022; Hung et al, 2021; Palumbo et al, 2022; Tavares & Azevedo, 2022; Young et al, 2019), with specific examples such as “there is a need for more empirical studies and quantitative research” (in the context of Industry 4.0 and Sustainability) (Mastrocinque et al, 2022) or the remark from (Grybauskas et al, 2022) about the “sheer lack of empirical evidence on the positive or negative impacts of Industry 4.0 on social sustainability”.…”
Section: Discussion and Future Research Agendamentioning
confidence: 99%
“…Most studies were done in the home setting (7/10, 70%), with two in a home-like lab setting and one in a lab setting. Studies in the lab-home involved monitoring sessions lasting between 1 hour and 7 days (Hung et al, 2021;Rahal et al, 2008;Tegou et al, 2019), while home-based monitoring ranged from 3 weeks to 18 months. Table 4 displays the outcomes from studies that included patient populations.…”
Section: Studies With Clinical Populationmentioning
confidence: 99%
“…Room detection accuracy ranged from 50-88% across three studies (Lach et al, 2019;Montoliu et al, 2020;Rahal et al, 2008), while one study reported failure rates of >15% for motion detectors and servers installed in the home (Hu et al, 2016). One study reported linear accuracies of 1.5-2.0m using wireless sensor networks within the home (Hung et al, 2021).…”
Section: Studies With Clinical Populationmentioning
confidence: 99%
See 2 more Smart Citations